2016
DOI: 10.1080/13603116.2016.1159254
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and comparison of Turkish and American preschool teacher candidates’ attitudes towards inclusion of young children with disabilities

Abstract: Inclusion of young children with disabilities into general education classrooms is a common practice that has been implemented for many years in developed countries around the world and many developing countries have been creating and implementing laws and regulations to support inclusive education in early years. Although extant literature includes a commonly agreed definition for inclusion, the implementation of inclusive practices varies across countries. A critical factor for successful implementation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
0
9
0
3
Order By: Relevance
“…Existing research has revealed that the attitudes and expectations of teachers have a direct effect on students' learning and development (McLeskey & Waldron, 2006;Forlin, Cedillo, & Romero-Contreras, 2010). Additionally, researchers have reported that the disabled teachers' positive attitudes and beliefs towards students in the inclusion environments is related to considerably improved inclusion practices and better student output (Berry, 2010, Blecker & Boakes, 2010, Darling-Hammond, 2006Rakap, & Kaczmarek, 2010;Rakap, Parlak-Rakap, & Aydin, 2016). It is believed that the teachers who have a positive attitude towards inclusion are able to use educational strategies in general education classes more effectively and they feel sufficiently competent in terms of meeting the requirements of students with special needs and adapting the curriculum and materials accordingly (Campbell, Gilmore, & Cuskelly, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has revealed that the attitudes and expectations of teachers have a direct effect on students' learning and development (McLeskey & Waldron, 2006;Forlin, Cedillo, & Romero-Contreras, 2010). Additionally, researchers have reported that the disabled teachers' positive attitudes and beliefs towards students in the inclusion environments is related to considerably improved inclusion practices and better student output (Berry, 2010, Blecker & Boakes, 2010, Darling-Hammond, 2006Rakap, & Kaczmarek, 2010;Rakap, Parlak-Rakap, & Aydin, 2016). It is believed that the teachers who have a positive attitude towards inclusion are able to use educational strategies in general education classes more effectively and they feel sufficiently competent in terms of meeting the requirements of students with special needs and adapting the curriculum and materials accordingly (Campbell, Gilmore, & Cuskelly, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that teacher candidates generally hold a positive attitude towards inclusion of young children with disabilities (Forlin, Sharma and Loreman, 2007;Lancaster and Bain, 2007;Rakap, Parlak-Rakap and Aydin, 2015;Sharma, 2012;Sharma, Ee and Desai, 2003;Sharma et al, 2006;Silverman, 2007). Studies have noted several factors that may influence the attitudes of teacher candidates.…”
Section: Introductionmentioning
confidence: 99%
“…When the studies related to inclusive education in pre-school are examined, it is seen that the most researched subject is the knowledge, attitude and opinions of teachers and teacher candidates towards inclusion of children with special needs into general education classrooms. Findings of these studies have shown that preschool teachers and teacher candidates generally possess a positive attitude towards inclusion (e.g., Artan and Uyanık-Balat, 2003;Gök and Erbaş, 2011;Rakap et al, 2016). However, the extant literature also includes studies reporting negative attitudes (e.g., Şahbaz and Kalay, 2010).…”
Section: Extended Summarymentioning
confidence: 99%